The Effect of Work Environment and Leadership on Employee Performance at the Kaur Regency Dprd Secretariat - Lias Mawati; Ida Anggriani; Yudi Irawan Abi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to determine the effect of the work environment on employee performance at the Kaur District DPRD Secretariat, to determine the effect of leadership on employee performance at the Kaur District DPRD, and to determine the effect of the work environment and leadership on employee performance at the Kaur District DPRD Secretariat. The method of collecting data in this study is using a questionnaire and the method of analysis is multiple linear regression. Based on the results of the study, it was found that the work environment had a significant effect on employee performance at the Kaur Regency DPRD Secretariat because the significance value was 0.000 <0.05. Leadership has a significant effect on employee performance at the Kaur Regency DPRD Secretariat because its significance value is 0.016 <0.05. The work environment and leadership simultaneously or jointly have a significant effect on employee performance at the Kaur Regency DPRD Secretariat because the significance value is 0.000 <0.05.